2022
DOI: 10.1002/smll.202203589
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Diatomic Catalysts: General Design Fundamentals and Diversified Catalytic Applications

Abstract: In recent years, some experiments and theoretical work have pointed out that diatomic catalysts not only retain the advantages of monoatomic catalysts, but also introduce a variety of interactions, which exceed the theoretical limit of catalytic performance and can be applied to many catalytic fields. Here, the interaction between adjacent metal atoms in diatomic catalysts is elaborated: synergistic effect, spacing enhancement effect (geometric effect), and electronic effect. With regard to the classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 209 publications
(435 reference statements)
0
45
0
Order By: Relevance
“…Dual-site single-atom catalysts (or diatomic catalysts) are expected to achieve effective regulation of multiple reaction processes (or synergistic catalytic effects of two sites). [144] Recently, Yu et al reported that atomically dispersed Fe-Ni dual atoms embedded in a N-doped carbon matrix (cubic carbon nanocages) (FeNi SAs/NC) were successfully developed with remarkable electrocatalytic activity in ORR and OER (see Figure 26 for details). [207] The FeNi NPs-NH 3 was obtained from FeNi-MOF/DPA by calcination at 500 °C for 2 h under an ammonia stream.…”
Section: Oermentioning
confidence: 99%
“…Dual-site single-atom catalysts (or diatomic catalysts) are expected to achieve effective regulation of multiple reaction processes (or synergistic catalytic effects of two sites). [144] Recently, Yu et al reported that atomically dispersed Fe-Ni dual atoms embedded in a N-doped carbon matrix (cubic carbon nanocages) (FeNi SAs/NC) were successfully developed with remarkable electrocatalytic activity in ORR and OER (see Figure 26 for details). [207] The FeNi NPs-NH 3 was obtained from FeNi-MOF/DPA by calcination at 500 °C for 2 h under an ammonia stream.…”
Section: Oermentioning
confidence: 99%
“…Apart from that, in recent years, diatomic catalysts (DACs) have arisen as a member of the monoatomic catalyst family. 191 By inserting the additional metal atom to produce homogeneous element DACs or heterogeneous element diatomic catalysts DACs, the linkage between the two metal atoms can efficiently overcome some of the limitations of SACs such as poor metal loading, a limited contact area between atoms and supporting materials, and weak interactions. 192,193 Thence, in contrast to monatomic catalysts, diatomic catalysts provide more atomic loading, engagement between diatomic sites, and a broader range of catalytic performances, especially boosted activity and product selectivity in the CO 2 RR.…”
Section: Photocatalytic Co 2 Rr By Mxene-based Photocatalystsmentioning
confidence: 99%
“…216 In addition to breaking the linear relationship between the adsorption strengths of individual reaction intermediates, the diatomic catalysts also inherit all the advantages of SACs, with increased metal loading and further adjustment of the catalyst's electronic structure. [217][218][219] DACs can be divided into two types depending on the catalytic centers: (i) mononuclear hetero-monoatomic; (ii) binuclear diatomic pairs. 220 Mononuclear hetero-monoatomic is the combination of two different metal center SACs, and the two metal centers are stochastically and independently distributed on the carrier.…”
Section: Dual-atom Catalystsmentioning
confidence: 99%